Предмет: Алгебра,
автор: 2014Ирина2014
Решить уравнение
Ответы
Автор ответа:
0
5*(х+7)-3*(2х+1)
------------------------- = 2
15
5*(х+7)-3*(2х+1) =2*15
5*(х+7)-3*(2х+1)=30
5х+35-6х-3=30
32-х=30
х=2
------------------------- = 2
15
5*(х+7)-3*(2х+1) =2*15
5*(х+7)-3*(2х+1)=30
5х+35-6х-3=30
32-х=30
х=2
Похожие вопросы
Предмет: Английский язык,
автор: konowmawa15
Предмет: Информатика,
автор: hwanghyunjin2002skz
Предмет: Английский язык,
автор: krasnovr84
Предмет: Обществознание,
автор: ksenyabasova0
Предмет: История,
автор: svetasvetlana5